Everybody wants to make money from them: a qualitative study on labor exploitation and labor trafficking of farmworkers in Michigan - Lisbeth Iglesias-Rios; Alexis J. Handal (Discover Social Science and Health)
Abstract Introduction Fair work conditions are essential for promoting health among workers, communities, and society. Yet, historically farmworkers have been impacted by precarious and exploitative work conditions. Given the scarce research in Michigan with farmworkers, in 2019 we developed the Michigan Farmworker Project (MFP), guided by community-based participatory principles and in partnership with state and local organizations. This study assesses qualitative data collected from the first study of the MFP, specifically perceptions, knowledge, and experiences related to exploitative work and labor trafficking. Method We employed a framework analysis approach with 56 in-depth interviews with farmworkers (migrant, seasonal, H-2 A) and stakeholders from different service areas (social, educational, health care, legal and outreach) in Michigan. Finding Findings show the following emergent themes: (1) deceptive recruitment, (2) abuse of worker social vulnerability, (3) exploitative and hazardous work conditions, (4) coercion and threats, (5) wage theft, (6) document retention, (7) isolation and employer control, (8) confinement and physical and sexual violence, (9) experiences and perceptions of labor trafficking, and (10) fragmented systems and policy failures, underscoring the need for integrated federal, state and local regulatory responses to anti-trafficking efforts. Conclusion Exploitation of workers can be prevented by an independent regulatory body that enforces accountability and transparency from employers throughout the employment process. Federal and state level efforts on policies that promote decent and fair employment are sustainable development goals needed to address labor exploitation.